Students’ Perception on Learning Technical Vocabulary through Ted-Ed Video-Assisted Vocabulary Self-Collection Strategy - Annisa Jasmin; Elih Sutisna Yanto (Universitas Pahlawan Tuanku Tambusai, 2021)
Vocabulary Self-collection Strategy (VSS) has been known as one strategy in teaching vocabulary which the combination of this strategy and video viewing activity is still underexplored. This narrative case study was to investigate the process of the use of TED-Ed video-assisted VSS on learning technical vocabulary and to report the students’ perception on the strategy with the eleventh grade students majoring science program as the respondence. The instruments were semi-structure interview for students and students’ VSS chart. The findings of this study found three main themes regarding to the students’ perception on TED-Ed video assisted VSS: (1) the advantages of TED-Ed video, (2) the efficacy of Vocabulary Self-collection Strategy (VSS), and (3) the students’ engagement in learning vocabulary through Vocabulary Self-collection Strategy (VSS). The utilizing TED-Ed video as the resource of teaching material or integrating it in the process of VSS can be considered by English teacher to teach context based vocabulary.